FOREIGN TRADE EXCHANGE OF AGRICURTURAL AND FOOD PRODUCTS OF SERBIA AND BOSNIA AND HERCEGOVINA : DOI: 10.5937/etp2403075P - Puškarić, Anton; Kuzman, Boris; Papić Blagojević, Nataša (Ekonomija - teorija i praksa, 2024)
The aim of the paper is to analyze the trends and structure of foreign trade in agricultural and food products between the Republic of Serbia and Bosnia and Herzegovina, classified according to the Standard International Trade Classification (SITC). The analysis covers section 0 - Food and live animals, section 1 - Beverages and tobacco, parts of section 2 - Crude materials, and section 4 - Animal and vegetable oils, fats and waxes. The research is based on available data for the period 2019-2023. The share of individual products in total exports and imports was examined using frequency analysis and variation intervals. In the exchange of agricultural and food products with Bosnia and Herzegovina, the Republic of Serbia achieved an average surplus of 442.4 million USD during the analyzed period. By commodity division, the largest surplus was seen in the exchange of cereals and cereal preparations, averaging 116.5 million USD, while the largest trade deficit was observed in the exchange of fish and processed products, averaging 5.2 million USD. The authors concluded that good export results were achieved during the observed period, with a growth rate of 6.20%